2012
DOI: 10.1590/s0100-40422012000200021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of a castor-oil based formulation in limiting pesticide residues in strawberry crops

Abstract: Recebido em 11/5/11; aceito em 4/8/11; publicado na web em 26/9/11 A study was made to evaluate the effect of a castor oil-based detergent on strawberry crops treated with different classes of pesticides, namely deltamethrin, folpet, tebuconazole, abamectin and mancozeb, in a controlled environment. Experimental crops of greenhouse strawberries were cultivated in five different ways with control groups using pesticides and castor oil-based detergent. The results showed that the group 2, which was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Kumar et al (2019) observed that recommended doses of castor, pongamia, sesame and neem oil and its formulated products did not cause any problem on tender cotton leaves. Galhiane et al (2012) showed that castor oil is non-phytotoxic at concentrations that are effective against mites and aphids. When the temperature is high throughout the day, the oil disappears more rapidly and phytotoxic symptoms are reduced in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al (2019) observed that recommended doses of castor, pongamia, sesame and neem oil and its formulated products did not cause any problem on tender cotton leaves. Galhiane et al (2012) showed that castor oil is non-phytotoxic at concentrations that are effective against mites and aphids. When the temperature is high throughout the day, the oil disappears more rapidly and phytotoxic symptoms are reduced in plants.…”
Section: Resultsmentioning
confidence: 99%
“…If one inspects the results from a bioeconomical and financial point of view, then it is evident that the optimal utilization of water-based solutions and bio-oils from the pyrolysis process to acquire biopesticides would involve lower costs and more straightforward processes. For example, the water-based solution distillate only requires filtration and dilution and the production of a biopesticide from a bio-oil distillate simply involves dilution, centrifugation, and filtration [ 56 , 57 , 58 ]. In the future, the driving force behind the development of novel biopesticides will be the legislation on what kind of materials can be used as pesticides.…”
Section: Resultsmentioning
confidence: 99%